2015
DOI: 10.1177/1521025115571091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Nonreturner Profiles to Inform the Development of Targeted College Retention Interventions

Abstract: Throughout the college retention literature, there is a recurring theme that students leave college for a variety of reasons making retention a difficult phenomenon to model. In the current study, cluster analysis techniques were employed to investigate whether multiple empirically based profiles of nonreturning students existed to more fully understand the types of students with particular characteristics that are related to leaving college. Based on over 18,000 students who left their initial institution aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…While previous studies have focused on the student perspective and have improved the understanding of student retention at the university level (e.g., Mattern, Marini, & Shaw, ; Slanger, Berg, Fisk, & Hanson, ), the engineering education community's understanding remains limited about the specific actions educators take to improve retention (Tinto, ). ESSCs offer examples of interventions that are offered to improve the retention of underrepresented students in engineering degree programs.…”
Section: Frameworkmentioning
confidence: 99%
“…While previous studies have focused on the student perspective and have improved the understanding of student retention at the university level (e.g., Mattern, Marini, & Shaw, ; Slanger, Berg, Fisk, & Hanson, ), the engineering education community's understanding remains limited about the specific actions educators take to improve retention (Tinto, ). ESSCs offer examples of interventions that are offered to improve the retention of underrepresented students in engineering degree programs.…”
Section: Frameworkmentioning
confidence: 99%
“…Despite these seemingly inconsistent findings, a meta-analysis found that female students earned higher grades in English and mathematics courses (Voyer & Voyer, 2014); even though male students scored relatively higher in mathematics on standardized admission tests, like ACT and SAT (Bielinski & Davison, 2001; DeMars, 2000; Liu & Wilson, 2009). Hence, at least on the basis of scoring better on standardized admission tests (Combs et al, 2010; Mattern, Shaw, & Marini, 2013; Smithwick-Rodriguez, 2011), these findings suggest that male students begin college more academically ready to succeed in mathematics, whereas female students are better prepared to succeed in English courses. However, there is ample evidence that female students earn significantly better grades in first-year English Composition and College Algebra (e.g., Conger & Long, 2010; Ding et al, 2007; Lorah & Ndum, 2013; Voyer & Voyer, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student departure from an institution due to academic dismissal tends to account for less than 25% of departures (Tinto, 1993), and there is very little retention research comparing characteristics and outcomes of students who have been academically dismissed from college to those leaving an institution voluntarily (Brost & Payne, 2011;Cherry & Coleman, 2010;Cogan, 2011;Ott, 1988). In other words, in the plethora of studies examining student predictors of attrition in college, the outcome of attrition is rarely parsed by voluntary and involuntary leavers (Cherry & Coleman, 2010;Mattern, Marini, & Shaw, 2015). This may be an artifact of student data availability in databases of college outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, in the plethora of studies examining student predictors of attrition in college, the outcome of attrition is rarely parsed by voluntary and involuntary leavers (Cherry & Coleman, 2010;Mattern, Marini, & Shaw, 2015). This may be an artifact of student data availability in databases of college outcomes.…”
mentioning
confidence: 99%